Social accounting & social responsibility reporting in the Jordanian industrial companies listed in Amman stock exchange market - AL-Hawatmah, Zaid (Array, 2018)
This study examines practice of social accounting and the reporting of social responsibility in the industrial Jordanian companies listed in Amman Stock Exchange. As operations of industrial companies have significant impact on the society, they should be accountable to the environment, and members of societies in which they operate. The method adopted to figure out the state of current social accounting and reporting practices was carried out by analyzing the annual reports of 30 randomly selected Jordanian industrial companies for the year 2016. The study found that 73% of industrial companies in Jordan are disclosing their activities of social responsibility in the annual reports. This study also found that 50% of these companies use the director’s reports as the main outlet for disclosing their activities related to social responsibility, 36% companies use the corporate social responsibility report and finally 14% are use the notes or schedule to financial statement to inform general people about their commitment to social responsibility. The study recommended that as there are many types and techniques of reporting, the Jordanian securities commission, as a government regulatory entity, should work on establishing uniformity for disclosing social accounting reports, and the outlet for such disclosure should be clearly specified.